Inteligencia interpersonal y empatía en niños de la Institución Educativa San Francisco de Asís, Iquitos 2022 - Cardozo Mozombite, Ingrid del Pilar (2023)
A brief summary of the research is presented, starting from the following question: What is the relationship between interpersonal intelligence and empathy in children of the San Francisco de Asis Educational Institution of Iquitos in 2022? The general objective was to establish a link between the students' IQ and their capacity for empathy. It was decided to conduct a field study with a bivariate cross-sectional design, and the type of research selected was relational. The 86 students enrolled in the school's preschool class served as both population and sample. Two observation sheets were prepared to collect the data; these instruments went through the expert validation process. The technique used in this process was observation. Given that rho=0.580**; Sig. 0.001, among the student body, we found a statistically significant correlation between IQ and empathic behavior. This supports the null hypothesis of the study and demonstrates the importance of the relationship between IQ and empathy among the students of the San Francisco de Asis Educational Institution of Iquitos, Peru 2022.